Major hepatectomy with or without pancreatoduodenectomy for advanced gallbladder cancer. Issue 5 (14th February 2019) - Mizuno, T; Ebata, T; Yokoyama, Y; Igami, T; Yamaguchi, J; Onoe, S; Watanabe, N; Ando, M; Nagino, M
Abstract: Background: The indications for major hepatectomy for gallbladder cancer either with or without pancreatoduodenectomy remain controversial. The clinical value of these extended procedures was evaluated in this study. Methods: Patients who underwent major hepatectomy for gallbladder cancer between 1996 and 2016 were identified from a prospectively compiled database. Postoperative outcomes and overall survival were compared between patients undergoing major hepatectomy alone or combined with pancreatoduodenectomy (HPD). Results: Seventy-nine patients underwent major hepatectomy alone and 38 patients had HPD. The patients who underwent HPD were more likely to have T4 disease ( P < 0·001), nodal metastasis ( P = 0·015) and periaortic nodal metastasis ( P = 0·006), but were less likely to receive adjuvant therapy ( P = 0·006). HPD was associated with a high incidence of grade III or higher complications ( P = 0·002) and death ( P = 0·037). Overall survival was longer in patients who underwent major hepatectomy alone than in patients who underwent HPD (median survival time 32 versus 10 months; P < 0·001). In multivariable analysis, surgery in the early period (1996–2006) ( P = 0·002), pathological T4 disease ( P = 0·005) and distant metastasis ( P < 0·001) were associated with shorter overall survival, and cystic duct tumour ( P = 0·002) with longer overall survival. Conclusion: Major hepatectomy alone for gallbladder cancer contributes to favourable overall survival with low morbidity and mortality, whereas HPD is associated with poor overall survival and high morbidity and mortality rates. HPD may eradicate locally spreading gallbladder cancer; however, the indication for the procedure is questioned from an oncological viewpoint. Graphical Abstract: The surgical and oncological value of major hepatectomy with or without pancreatoduodenectomy for advanced gallbladder cancer was evaluated. Major hepatectomy alone (hep) was associated with acceptable overall survival and is recommended for locally advanced gallbladder cancer. In contrast, major hepatectomy with pancreatoduodenectomy (HPD) was associated with high morbidity and mortality rates, and poor postoperative survival. Added value of pancreatoduodenectomy questionable